Supply chain leadership developing a people-centric approach to effective supply chain management - Robertson, Peter W. (Routledge, 2022)
Presents a fresh, people-centered approach, to Supply Chain Leadership, with a focus on training and developing those in marc:leadership positions. Features textbook pedagogy to aid learning throughout, including worked examples explaining different analytics techniques, international case studies, review questions and supplementary online resources. Suitable for use on Supply Chain Management and Operations Management courses globally, as well as in executive education